The Role of Art in the Development of Inclusive Education - Ganiyevich, Davlatov Oybek (International Journal of Membrane Science and Technology, 2023)
The article reveals the essence of regulatory documents for the development of inclusive education, information about foreign experience in working with children with disabilities. Therefore, the pedagogical and psychological aspects of inclusive education and the possibilities of using art as a tool in the educational process will be discussed.